Navigating beyond the surface - prognostic significance of KRAS, NRAS, BRAF, PIK3CA, and TP53 mutations examined by exons - Afrăsânie, Vlad Adrian; Marinca, Mihai Vasile; Gafton, Bogdan; Rusu, Alexandra; Froicu, Eliza Maria; Sur, Daniel; Lungulescu, Cristian Virgil; Popa, Raluca Cezara; Afrăsânie, Irina; Ivanov, Anca Viorica; Gîlcă-Blanariu, Georgiana Emmanuela; Miron, Lucian; et al. (Frontiers in Oncology, 2025)
IntroductionMetastatic colorectal cancer (mCRC) is a disease with various molecular profiles that exhibit different evolution patterns. Although most mCRC patients receive the same chemotherapy drugs in the first-line setting, treatment response is heterogeneous suggesting some tumors are inherently resistant to oxaliplatin/fluoropyrimidine regimen. Genomic-based markers may help identify these patients and guidetreatment decisions due to potential prognostic and predictive value.MethodsWe performed a retrospective analysis on 77 patients diagnosed with mCRC treated with an oxaliplatin/fluoropyrimidine regimen in the Regional Institute of Oncology Iaşi between April 2017 and December 2019. We studied the impact of KRAS, NRAS, BRAF, PIK3CA and TP53 genes and their mutations in a treatment-naive population.ResultsThe median progression free survival (PFS) was 11 months (95% CI, 10.2-11.7 months) and the median overall survival (OS) was 23.6 months (16.3-30.8 months). Multivariate analysis of factors affecting PFS revealed that KRAS exon –3 mutation was associated with quicker progression while on oxaliplatin-based chemotherapy. A similar analysis indicated that the KRAS exon –3 mutation was also associated with decreased OS (p=0.03). The presence of the TP53 in exon 8 was associated with an increased OS (p=0.001).DiscussionThe present analysis offers insights into the prognostic implications of genes and exon-distributed mutations within RAS, BRAF, PIK3CA, and TP53 in mCRC. Subsequent prospective investigations with a more extensive patient cohort are needed to clarify the influence of exon-distributed mutations on therapeutic decision-making and prognostic outcomes.